Aluminum Acceleration and Reaction Characteristics for Aluminized CL‐20‐Based Mixed Explosives. Issue 6 (16th May 2018) - Liu, Danyang; Chen, Lang; Wang, Chen; Wu, Junying
Abstract: The effects of aluminum mass content and particle size in CL‐20‐based aluminized explosives were investigated with a small‐scale confined plate push test. The confinement strength of the detonation products was enhanced to twice that of cylinder tests to accelerate the aluminum particle reaction. An all‐fiber displacement interferometer system for any reflector was used to continuously measure the plate velocity over time. A series of aluminized explosives containing various aluminum particle masses and sizes were tested, as well as explosives containing LiF instead of aluminum. Numerical simulations of explosive detonation and metal plate acceleration were performed, where parameters for the equation of state of the detonation products were calibrated by comparing the results with experiment. The results indicated that most of the aluminum particles (including 200‐nm diameter particles) reacted with the detonation products after the Chapman‐Jouguet point. Moreover, the released energy from the reaction could further accelerate the metal plate and increase the acceleration time, although the initial plate velocity was reduced. The start reaction times of small particles were earlier than that of larger particles. Specifically, 2‐50‐μm aluminum particles start to react when the volume of detonation products expanded to 1.24 times the initial volume, while the 200‐nm particles start to react at 1.07 times the initial volume, with a significantly higher reaction rate. The reaction rates decreased with increasing mass fraction of reacted aluminum and a decrease in pressure. Abstract :